MULTIVARIATE ANALYSIS ON CRANIUM MEASUREMENTS OF THREE BREEDS OF GOAT IN CENTRAL JAVA - Suryani, H.F.; Purbowati, E.; Kurnianto, E. (Diponegoro University, 2013)
The purposes of this study were to 1) identify the size and shape of cranium of three breeds ofCentral Java local goats (Kejobong, Kacang and Ettawa Grade), 2) examine the effectiveness ofmultivariate analysis of cranial measurement and 3) estimate genetic distance among three local breedsof goat. The material used was cranium from female Kejobong, Kacang and Ettawa Grade goats, agedfor about 4 years (determined on the basis based on eruption of teeth), the number of specimens were30; 10 and 10, respectively. Twenty seven cranial measurements used to data observed, multivariateanalysis of GLM, CANDISC, PRINCOMP and DISCRIM were used to analysis all data observed.UPGMA of MEGA 5 was used to illustrate the distance among breeds. Results showed that EttawaGrade tended to show the largest size, followed by Kejobong and Kacang goats. Kejobong goat showedsmall cranium size with large cranium shape. Different things was found in Kacang goats in whichcranium size and cranium shape are relatively small. Kacang breed showed the smaller size (PrincipalComponent I or PC-1 = -2) compared to Ettawa Grade (PC-I = 3) and Kejobong goat (PC-I = -1).Analysis for classifying three breeds of local goat resulted in high accuracy (100%) as indicated by 0%of erroneous level (0%). Kejobong goat was close to in the genetic relationship to Kacang goatcompared to Ettawa Grade goat.